2013
DOI: 10.1111/coa.12189
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and associated factors in persons with chronic rhinosinusitis in the general population: A prospective questionnaire and clinical cross‐sectional study

Abstract: This study gives insight into health-related quality of life and objective findings in persons with chronic rhinosinusitis recruited from the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 17 publications
6
69
0
3
Order By: Relevance
“…Looking at the wider picture, one international study demonstrated that one in three CRS patients in primary care has poorly controlled symptoms; the feedback from our participants in the qualitative substudy also highlighted poor symptom control as a problem. The rhinosinusitis commissioning guidelines produced by ENT UK in conjunction with the Royal College of Surgeons of England recommend that CRS patients have received ND and INCS for 3 months before referral to secondary care, and this is derived from the European position paper of which there is a summary version for GPs.…”
Section: Discussionmentioning
confidence: 84%
“…Looking at the wider picture, one international study demonstrated that one in three CRS patients in primary care has poorly controlled symptoms; the feedback from our participants in the qualitative substudy also highlighted poor symptom control as a problem. The rhinosinusitis commissioning guidelines produced by ENT UK in conjunction with the Royal College of Surgeons of England recommend that CRS patients have received ND and INCS for 3 months before referral to secondary care, and this is derived from the European position paper of which there is a summary version for GPs.…”
Section: Discussionmentioning
confidence: 84%
“…The resulting scores range from 0 to 110, and the median score in a normal population without CRS ranges between 6.5 and 7 in published studies. 3,8,15 The SF-12 questionnaire (a condensed version of the SF-36) is a The EQ-5D-5L is a standardised measure of health status consisting of a visual analogue scale (VAS) to assess patient-reported health state on the day of completing the survey (0=worst imaginable health state and 100=best imaginable health state) in addition to a questionnaire with five dimensions (mobility, self-care, usual activities, pain/discomfort and anxiety/depression) (EuroQol 2011). 16 Each of the dimensions asks for a response that corresponds to a health status level of no problems, slight problems, moderate problems, severe problems and extreme problems that are coded level 1-5, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Lange et al published health utility assessments from the trans‐European GALEN study that showed a lower health‐related quality of life using the EQ‐5D‐3L in CRS patients compared to those without CRS . A recent study in the USA reported a lower health utility value (also generated by the EQ‐5D) for patients with CRS compared to the general population, the value was similar to that of other chronic diseases such as mild asthma and migraine .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A large multicentre study based on questionnaires has shown an overall prevalence of CRS at 10.9 % in Europe [2], and in a recent Danish study the CRS prevalence was 8.5 % [3]. The high prevalence of CRS covers a broad spectrum of disease severity.…”
Section: Introductionmentioning
confidence: 96%